Education Methods In The Perspective Of Islamic Education Philosophy - Risqi Risqi; Alwi Alwi (Proceeding International Seminar of Islamic Studies, 2019)
Our article is titled Education Methods In The Perspective Of Islamic Education Philosphy. Very component in Islamic education, what methods are recommended in Islamic education? In Islamic education there are methods that are good and right, including; Methods of lecture, discussion, question and answer, and exemplary. The method used in this article is the library research method. based on the method above is highly recommended to educators, both Islamic and general educators, so that the creation of intelligent students, and this method is very useful in learning an educator, in delivering lessons to students, in the philosophy of education also very much requires educational methods and in the method of Islamic education itself in dire need of learning Islamic education philosophy, both of which are interrelated and complementary.